INVESTIGATION OF TRANSIENTS IN SYSTEMS OF SUBORDINATE REGULATION OF SPEED OF AN ENGINE OF A DIRECT CURRENT WITH INTENSITY DETECTOR - Михайлова, Л. М.; Камишлов, В. Г.; Дубік, В. М.; Горбовий, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The study presents the method of calculation of transients in the technically optimal [2] at speed (e.m.f.) systems with intensity detectors for controlling actions in the direct current drives A comprehensive analysis of the dynamical systems is given by differential equations, the order of which corresponds to the order of differential equations, which describe the corresponding systems. Moreover, the authors proceed from the assumption that the analytical calculations of automatic control systems allow readers to get more complete information on the transients in these systems. The analytical dependencies for all the DC drives considered in the work are provided.In the study of high order systems, a simplified differential equation may allow errors in the calculation of such parameters of the system as the magnitude of the maximum and the rate of increase of anchor current, when selecting the installed power of the converters and, in particular, their voltages. In more in-depth studies related to the formation of current diagrams of the anchor current, as well as in the calculation of the equalization current in dependent control systems. Also, errors can reach large values, since in these cases derivatives of high orders from the main function are used